Variability and interrelation of breeding-valuable traits of varieties and lines of spring soft wheat in the conditions of the Middle Volga region - I. F. Demina (Аграрная наука Евро-Северо-Востока, 2023)
The article presents the results of a three-year study (2020-2022) of 16 varieties and 17 breeding lines of spring soft wheat bred by the Federal Scientific Center for Bast Fiber Crops in the soil and climatic conditions of the Penza region. The crop productivity in the experiment varied between 1.77-4.15 t/ha. Seven samples demonstrated the highest productivity: Nastavnik, Eritrospermum 70/04-3, Irvita, Sensei, Eritrospermum 20/08-7, Lutestsens 1/12-19, Eritrospermum 15/08-4, which exceeded the standard variety Arkhat by 0.27-0.71 t/ha. During the studies the yield was related to the average variable trait (CV =11.9-19.5 %). The variation of the duration of the growing season of the studied spring wheat samples averaged 81-93 days. It was shorter in 2021 (from 67 to 80 days), the longest in 2022 (from 91 to 100 days). The height of spring soft wheat plants in the studies was a low-variable feature (CV = 3.4-8.5 %) and averaged 82.1-100.2 cm over the years. The ear grain content varied from 18 pieces in the Erythrospermum 25/08-11-18 in 2022 up to 40 pieces in the Nastavnik variety in 2021. The trait was medium-variable (CV = 11.3-18.5 %). The highest average productivity of an ear was noted in 2022 – 1.08 g, and the lowest in 2020 – 0.92 g. The high mass of grain per ear was noted in Nastavnik variety – 1.40 g, Eritrospermum 70/04-3 – 1,38 g, Irvita – 1.35 g, which were characterized by high yield. Eritrospermum 70/04-3, Eritrospermum 20/08-7 and Irvita selected by the genotype productivity were characterized by bulky grains of 40.6-43.2 g. A significant correlation was observed between the yield and the grain weight per plant (r = 0.908...0.924, P≤0.001). The studied patterns can be used in ecological breeding of soft spring wheat.